SISTEM GADAI TANAH SAWAH PERSPEKTIF HUKUM POSITIF UU NO.56/PRP/TAHUN 1960 DI DESA BANYUPUTIH KECAMATAN BANYUPUTIH KABUPATEN SITUBONDO. - Jonwari; Faiz Zainuddin (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2020)
Pawning of land often occurs among the community, the reason for mortgaging their rice fields is because there is an urgent need. The collateral is processed and used by murtahin. In Islamic law regarding the use of pawning collateral there are so many opinions from the scholars'. Taking back the land by paying money equal to the amount of the debt, as long as the debt has not been paid off, the paddy field remains in the control of the murtahin regardless of how long the pawning is carried out. The focus of the aim of this study is to determine the paddy field pawning system according to Law no. 56 Prp of 1960 concerning the determination of the agricultural area for paddy field pawning. To answer the focus of the research objectives, this study used a qualitative descriptive method with a synthetic legal approach (guide) between normative legal research and empirical legal research. Based on the results of this study, it can be seen that the paddy field pawn system in Banyuputih Village, Banyuputih District, Situbondo Regency, the pawn giver comes to the pawn recipient to pawn the land, after the pawn recipient agrees, the collateral in the form of paddy land is managed and manipulated by the pawn recipient until the deadline. which has been specified. After arriving at the time of redemption, the pawker redeems with a nominal amount of the loan. According to Law no. 56 Prp of 1960 concerning the determination of the agricultural area of ​​the paddy field pawning system is contrary to the existing regulations.